A methodological rejoinder to "Does income relate to health due to psychosocial or material factors?". (August 2020) - Stark, Oded; Jakubek, Marcin
Abstract: There is a presumption that when an individual's comparison of his income with the incomes of others in his comparison group yields an unfavorable outcome, the individual is dismayed and experiences stress that impinges negatively on his health. In a recent study, Hounkpatin et al. (2016) conduct an inquiry aimed at deciphering which measure of low relative income reflects better the adverse psychosocial effect of low relative income on health. Hounkpatin et al. pit against each other two indices that they characterize as "competing:" the "relative deprivation (Yitzhaki Index)" of individual i, R D i ; and the "income rank position" of individual i, R i . In this Rejoinder we show that because a measure of rank is embodied in the R D i index and the R i index can be elicited from the R D i index, these two indices need not be viewed as competing. Furthermore, we formulate a composite measure of relative deprivation, C R D i, which can be used to assess more fully the psychosocial effect of individual i 's low relative income on his health.